Co-occurrence of motor problems and autistic symptoms in attention-deficit/hyperactivity disorder - Reiersen, Angela M; Constantino, John N; Todd, Richard D (Journal of the American Academy of Child and Adolescent Psychiatry, 2008)
To investigate the relation between parent reports of motor problems and clinically significant autistic symptoms in children with and without attention-deficit/hyperactivity disorder (ADHD). Subjects were male (n = 521) and female (n = 330) twins from an epidemiological study of ADHD, ages 7 to 19 years at assessment using the Child Behavior Checklist and semistructured psychiatric diagnostic interviews. Parent-rated Social Responsiveness Scale questionnaires were returned for 62% of 1,647 individuals who participated in interviews. After exclusion of subjects with incomplete data or evidence of mental retardation, 851 subjects (52%) were available for the present study analysis. Each subject was classified by DSM-IV ADHD subtype and assigned to one of seven population-defined ADHD subtypes based on latent class analysis of DSM-IV ADHD symptoms. Within each ADHD subtype, we examined the relation between Child Behavior Checklist motor problem endorsement and elevated autistic symptoms on the Social Responsiveness Scale. Motor problems and high levels of autistic traits were most common in individuals with combined-type ADHD. Within each of the clinically relevant DSM-IV and latent class ADHD subtypes, individuals with the combination of motor problems and ADHD were more likely to have high levels of autistic traits than those with ADHD alone. Children with the combination of ADHD and parent-reported motor coordination deficits have elevated levels of autistic symptoms. Targeted treatment and prevention interventions may be warranted. The exclusion criteria for DSM-IV ADHD should be revised to reflect these population-based findings.